PEMBINAAN PEMENUHAN HAK ASASI LINGKUNGAN SEBAGAI HARMONISASI MANUSIA DAN LINGKUNGAN PERSPEKTIF AL-QUR’AN DI MAJLIS TA’LIM MUSLIMAT, BEKASI - Nur Arfiyah Febriani; Najwah Arsyad; Lu’lu’atil Chilmiyah; EE Junaedi Sastradiharja; Badru Tamam; Hani Fazlin (MPP: Lembaga Penelitian Dan Studi Kebijakan, 2024)
This study examines the fulfillment of environmental human rights as a form of harmony between humans and the environment from the perspective of the Qur'an. The increasingly alarming environmental degradation caused by human irresponsibility in utilizing natural resources forms the background of this research. This paper adopts a library research method by reviewing primary and secondary sources, including the Qur'an, classical exegesis works, and contemporary academic studies. The findings reveal that the Qur'an positions humans as stewards (khalifah) on earth, entrusted with the responsibility to preserve and cultivate the environment as part of the divine mandate. Environmental human rights necessitate treating nature with respect as a partner in humanity’s devotion to God. The Qur’anic principles of ecotheology emphasize that environmental balance is a prerequisite for human survival. The Qur'an provides ethical foundations for environmental preservation through the prohibition of causing harm and destruction (QS al-A’raf/7:56) and the command to utilize natural resources proportionally (QS al-Jumu’ah/62:10). Using a maqashid al-shari'ah approach, environmental protection is intrinsically linked to the preservation of religion, life, intellect, lineage, and property. This study asserts that humans, as part of the ecosystem, do not hold absolute rights over nature, but are obliged to maintain environmental balance and sustainability as a manifestation of their stewardship. It is hoped that this work can serve as a reference for strengthening the Islamic ecotheological paradigm in support of modern environmental conservation efforts